Empowering Refugee Families of Students with Disabilities - Warsi, Sadia; Fitzgerald, Karen (Journal of the American Academy of Special Education Professionals, 2020)
Many refugee students with disabilities are entering their American classrooms for the first time after experiencing adversity and trauma. They may have experienced famine, war, displacement, forced migration and abuse. One can also presume that their special education needs were neglected due to the limited resources that were available to them. While some of these students will have apparent disabilities, others will have social-emotional and other disabilities that are hidden. As the special education team prepares to embark on welcoming and educating each of these students, they will first need to empower the parents.